A Model for Research-Based Mentorship and Professional Development - Matthew Lee Smith (New Prairie Press, 2019)
This article has no abstract. It serves as the editorial/overview for the special issue on mentorship. However, rather than simply introducing the special issue, a mentorship model is provided. As such, a commentary article type was selected.